THE EFFECTIVENESS OF HOTEL TAX REVENUE AND ITS CONTRIBUTION TO THE INCREASE OF LOCAL ORIGINAL REVENUE IN BANJARMASIN CITY - rukman rukman (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: The Role of Local Original Revenue (PAD) in Regional Income as a Reflection of Regional Financial Capability in Governance and Development. The role of Local Original Revenue (PAD) in regional income reflects the success of efforts or the financial capability of a region in funding governance and development. This study aims to analyze the contribution of hotel tax revenue to the Local Original Revenue (PAD) of Banjarmasin City and assess the effectiveness of the hotel tax collection system. Method: This study employs a quantitative approach. The population and sample consist of hotel tax data from 2019 to 2023. A descriptive quantitative analysis method is used in this research. Results: Overall, the contribution of hotel tax revenue from 2019 to 2023 has significantly supported Local Original Revenue (PAD), influencing the total PAD received. Novelty: This study highlights the necessity for local governments to establish clear regulations to set precise targets for regional tax revenue, particularly in the hotel tax sector.